PENINGKATAN KOMPETENSI GURU MADRASAH MENUJU ERA PENDIDIKAN 4.0 - PADLI PADLI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
Teachers as spearheads in the field of education must be willing to change and keep up with the times in order to be able to provide education to students in facing the education era 4.0. This research is a literature review (literature study), namely reviewing journals that are relevant to the theme which is the teacher's attempt to improve the competence of madrasa teachers in facing the education era 4.0. Teachers as teaching staff who are directly in contact with students must develop knowledge by increasing competence in using digital equipment for learning, being innovative in processing and delivering learning to students who focus on students. Competency development can be carried out independently or following programs implemented by the government. This research was carried out at the State Madrasah Intidaiyah (MIN) 1 Kapuas with the observation method (observation). The results of the study show that the efforts made by teachers at MIN 1 Murung Raya in order to improve teacher competence as a response to education 4.0, namely teachers as agents of change, teachers are able to build the character of students as shields in dealing with the negative effects of technological advances, teachers who are active in the community as a forum for sharing information and creative and innovative teachers in learning characterized by teachers who master contextual learning and independent learning. ABSTRAKGuru sebagai ujung tombak dalam bidang pendidikan harus mau berubah dan mengikuti perkembangan zaman agar mampu memberikan edukasi kepada peserta didik dalam menghadapi era pendidikan 4.0. Penelitian ini merupakan literatur review (studi Pustaka) yaitu mereview jurnal yang relevan dengan tema yang merupakan usaha guru dalam meningkatkan kompetensi guru madrasah dalam menghadapi era pendidikan 4.0. Guru sebagai tenaga pengajar yang langsung bersentuhan dengan peserta didik harus mengembangkan pengetahuan dengan meningkatkan kompetensi dalam menggunakan peralatan digital untuk pembelajaran, inovatif dalam mengolah dan menyampaikan pembelajaran kepada peserta didik yang berfokus pada peserta didik. Pengembangan kompetensi bisa dilakukan secara mandiri ataupun mengikuti program yang dilaksanakan oleh pemerintah. Penelitian ini dolaksanakan di madrasah intidaiyah negeri (MIN) 1 Kapuas dengan metode observasi (pengamatan). Hasil penelitian menunjukkan bahwa upaya yang dilakukan guru di MIN 1 Murung Raya dalam rangka meningkatkan kompetensi guru sebagai respon pendidikan 4.0 yaitu guru sebagai agen perubahan, guru mampu membangun karakter peserta didik sebagai tameng dalam menghadapi efek negative dari kemajuan teknologi, guru yang aktif di komunitas sebagai wadah berbagi informasi dan guru kreatif dan inovatif dalam pembelajaran yang ditandai dengan guru yang menguasai pembelajaran kontekstual dan merdeka belajar.